CD8 T Cells Target Antigen Cross-Presented by Bone Marrow Derived Cells to Induce Bystander Rejection of Grafts Lacking the Cognate Peptide-MHC. (November 2022) - Al-Adra, David P.; Thangavelu, Govindarajan; Lin, Jiaxin; Chan, William F.N.; Ellestad, Kristofor K.; Boon, Louis; Anderson, Colin C.
CD8 T cells play a key role in cancer immunotherapy and allograft rejection. However, it is not clear how they kill cells and tissues that do not have the agonist peptide-major histocompatibility complex (MHC) on their surface, as in the settings of MHC class I deficient tumors and indirect rejection of MHC-mismatched transplants. CD8 T cells might respond to agonist antigen cross-presented on hematopoietic cells, leading to a "bystander" rejection. Alternatively, they may recognize agonist antigen cross-presented on recipient endothelial cells and kill the tissue's vital blood supply. The latter mechanism predicts that all non-vascularized grafts, grafts dependent on in-growth of recipient blood vessels, will be susceptible to CD8 T cell mediated indirect rejection. In contrast, we show here that non-vascularized transplants, bearing the same agonist antigen, are not universally susceptible to this rejection pathway. Non-vascularized skin, but not islet or heart tissue transplants were indirectly rejected by CD8 T cells. Furthermore, CD8 T cells were able to indirectly reject skin grafts when recipient MHC class I expression was restricted to bone marrow derived cells but not when it was restricted to radioresistant cells (e.g. endothelial cells). These findings argue against a major role for endothelial cell cross-presentation in killing of tissue that does not present the agonist peptide-MHC class I. Instead, the data suggests that cross-presentation by recipient hematopoietic cells underlies the CD8 T cell mediated killing of tissue that is unable to directly present the target peptide-MHC class I.